A meta-analysis of biomarkers related to oxidative stress and nitric oxide pathway in migraine. (September 2015) - Neri, Monica; Frustaci, Alessandra; Milic, Mirta; Valdiglesias, Vanessa; Fini, Massimo; Bonassi, Stefano; Barbanti, Piero
Background: Oxidative and nitrosative stress are considered key events in the still unclear pathophysiology of migraine. Methods: Studies comparing the level of biomarkers related to nitric oxide (NO) pathway/oxidative stress in the blood/urine of migraineurs vs. unaffected controls were extracted from the PubMed database. Summary estimates of mean ratios (MR) were carried out whenever a minimum of three papers were available. Nineteen studies were included in the meta-analyses, accounting for more than 1000 patients and controls, and compared with existing literature. Results: Most studies measuring superoxide dismutase (SOD) showed lower activity in cases, although the meta-analysis in erythrocytes gave null results. On the contrary, plasma levels of thiobarbituric acid reactive substances (TBARS), an aspecific biomarker of oxidative damage, showed a meta -MR of 2.20 (95% CI: 1.65–2.93). As for NOs, no significant results were found in plasma, serum and urine. However, higher levels were shown during attacks, in patients with aura, and an effect of diet was found. The analysis of glutathione precursor homocysteine and asymmetric dimethylarginine (ADMA), an NO synthase inhibitor, gave inconclusive results. Conclusions: The role of the oxidative pathway in migraine is still uncertain. Interesting evidence emerged for TBARS and SOD, and concerning the possible role of diet in the control of NOx levels.